Synthesis and In Vitro Antibacterial Activity of Novel 3-Azabicyclo[3.3.0]octanyl Oxazolidinones - Bhattarai, Deepak; Lee, Sun H.; Seo, Seon H.; Nam, Ghilsoo; Kang, Soon B.; Pae, Ae N.; Kim, Eunice E.; Oh, Taegwon; Cho, Sang-Nae; Keum, Gyochang (WILEY, 2012)
We synthesized a series of oxazolidinone-type antibacterials in which morpholine C-ring of linezolid has been modified by substituted 3-azabicyclo[3.3.0]octanyl rings. Acetamide or 1,2,3-triazole heterocycle was used as C-5 side chain of oxazolidinone. The resulting series of compounds was then screened in vitro against panel of susceptible and resistant Gram-positive, Gram-negative bacteria, and Mycobacterium tuberculosis (Mtb). Several analogs in this series exhibited potent in vitro antibacterial activity comparable or superior to linezolid against the tested bacteria. Compounds 10a, 10b, 11a, and 15a displayed highly potent activity against M.similar to tuberculosis. Selected compound 10b showed good human microsomal stability and CYP-profile, and showed low activity against hERG channel.
Keywords: RESISTANT STAPHYLOCOCCUS-AUREUS; LINEZOLID-RESISTANT; MYCOBACTERIUM-TUBERCULOSIS; MULTIDRUG-RESISTANT; MURINE MODEL; AGENTS; INFECTIONS; EPIDERMIDIS; SYSTEM; GENE